MENGOPTIMALISASIKAN SISTEM PENGARSIPAN SECARA DIGITAL PADA KANTOR DISTRIK NAVIGASI TIPE A KELAS II BENOA - Utami, Ni Made Satya; Merlin, Ni Kadek Merliyana Putri (Jurnal Abdi Citra, 2025)
The Benoa Class II Navigation District Office is a Technical Implementation Unit that is under and responsible to the Directorate General of Sea Transportation which still implements a manual archive system to store and manage various important administrative documents. However, there are challenges at the Benoa Type A Class II Navigation District office in managing the archive system that needs to be improved immediately. This service activity aims to provide training and socialization related to the importance of using digital archives using storage on laptops or cloud-based systems. The solution to overcome this challenge is to introduce the use of a more sophisticated digital archive management system integrated with computer storage (cloud storage), better data retrieval technology and organize digital archives with a clear and consistent folder system based on specific categories, such as document type, year, or departmental relevance. This work program is expected to help agencies to improve operational efficiency and effectiveness in document management in the Type A Navigation District Class II Benoa.